1994
DOI: 10.1029/94gl01579
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid simulation of contact discontinuity

Abstract: Contact discontinuities in a collisionless plasma are studied by hybrid simulations, in which ions are treated as particles and electrons are considered as a fluid. It is demonstrated that contact discontinuity with a stable density ramp can exist in cases with a finite electron temperature. An electron pressure gradient is present across the contact discontinuity, leading to the presence of a parallel electric field and hence field‐aligned potential increase (ΔΦ∥) in the transition region. By reflecting ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 10 publications
(8 reference statements)
5
17
0
Order By: Relevance
“…Their hybrid simulation results are similar to the one obtained by Wu et al [1994]. But their full particle code simulation showed that the CD structure is unstable in the ion time scale.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…Their hybrid simulation results are similar to the one obtained by Wu et al [1994]. But their full particle code simulation showed that the CD structure is unstable in the ion time scale.…”
Section: Introductionsupporting
confidence: 74%
“…[34] In summary, the stability of a CD, a long-term controversial issue [Wu et al, 1994;Lapenta and Brackbill, 1996], is reexamined analytically and numerically in this paper. Our analysis shows that the electron and the ion temperature profiles must be out of phase across the CD if the CD structure is to be stable in the electron time scale and with zero electron heat flux on either side of the CD.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations